Dementia Friendly Hospital Design: Key Issues for Patients and Accompanying Persons in an Irish Acute Care Public Hospital. (January 2020) - Xidous, Dimitra; Grey, Tom; Kennelly, S. P.; McHale, Cathy; O'Neill, Desmond
Objectives: Research was conducted to investigate the impact of the hospital environment on older people including patients with dementia and their accompanying persons (APs). The article presents key research findings in the case study hospital. Background: For many patients, the hospital is challenging due to the busy, unfamiliar, and stressful nature of the environment. For a person with dementia, the hospital experience can be exacerbated by cognitive impairment and behavioral or psychological symptoms and can therefore prove to be a frightening, distressing, and disorientating place. Method: The findings are based on a stakeholder engagement process where the research team spent approximately 150 hr observing within the hospital, administered 95 questionnaires to patients and/or APs, and conducted 12 structured interviews with patients and APs. A thematic analysis was employed to analyze and generate key themes emerging from the process. Results: Themes were grouped into overarching issues and design issues across spatial scales. Conclusion: This research confirms the negative impact of the acute hospital setting on older people with cognitive impairments including dementia and delirium. The multiple perspectives captured in this study, including most importantly people with dementia, ensure that stakeholder needs can be used to inform the design of the hospital environment. The research points to the value of understanding the lived experience of the person with dementia and APs. The voices of patients, particularly persons with dementia and their APs, are a crucial element in helping hospitals to fulfill their role as caregiving and healing facilities.